The Impact of Cézanne in Early Cubism - Mallen, Enrique (International Journal of Culture and History, 2024)
The 1907 Salon d’Automne included a Cézanne retrospective. Comprising fifty-six of his works, most of them oils, it featured a group of late paintings, among them some nominally “unfinished.” It had not been until his final years that the painter had begun to have wider public appeal. Now he had become the focus of attention of the avant-garde. Leo Stein recounted this transformation: “Hitherto Cézanne had been important only for the few; he was about to become important for everybody. At the Salon d’Automne of 1905 people laughed themselves into hysterics before his pictures, in 1906 they were respectful, and in 1907 they were reverent. Cézanne had become the man of the moment.” And Picasso would say: “For us, Cézanne was like a mother who protects her children ... He was my one and only master ... I’ve spent years studying his pictures ... Cézanne! He was as you might say a father to us all. It was he who protected us.” The article explores the influence the Master of Aix had on both the Spaniard and his French colleague Georges Braque as they developed the ideas of what would become Cubism.